Difference in corn kernel moisture content between pre- and post-harvest - Lu-lu LI; Bo MING; Jun XUE; Shang GAO; Ke-ru WANG; Rui-zhi XIE; Peng HOU; Shao-kun LI (Journal of Integrative Agriculture, 2021)
The harvest method of shelling corn (Zea mays L.) kernels in the field decreases labor costs associated with transporting, drying and threshing the crop. However, it was previously found that the kernel moisture content increased after field harvest, which decreased the value of corn kernels. To identify the reasons underlying the increase, we conducted a multiyear and -area trial in the Huang-Huai-Hai Plain, China and performed a staged-harvest test at several phases of kernel dry-down. The test investigated a range of parameters such as the kernel moisture content pre- and post-harvest, the kernel breakage rate, the amount of impurities, and the moisture content of various other plant tissues. An analysis of 411 pairs of pre- and post-harvest samples found that kernel moisture content after harvest was 2.2% higher than that before harvest. In the staged-harvest test, however, a significant increase was only observed when the kernel moisture content before harvest was higher than 23.9%. The increase in post-harvest kernel moisture content was positively associated with the pre-harvest kernel moisture content, breakage rate and impurity rate. Typically, at harvest time in this region, there is a significant fraction of immature crops with a high moisture content, resulting in kernels that are prone to breakage or impurities that ultimately lead to increases in water content after harvest. Therefore, we suggest using hybrids that quickly wither late in the growing stage. Additionally, farmers should delay harvest in order to minimize the pre-harvest kernel moisture content and thus reduce breakages and impurities, thereby improving the quality of kernels after harvest and the efficiency of corn kernel farming in China.